Merz: Revolusi seni yang membongkar batasan tradisi - Setiyawan, Danu; Sugiarti, Yati (Universitas Negeri Yogyakarta, 2025)
Merz, pioneered by Kurt Schwitters, advocates for the liberation from the artistic rules that confine it, making it a revolution in the field of art, particularly in German literature. Schwitters depicted this liberation through the representation of traditional and modern visions in his first Merz poem,